Incorporation of caprylic acid into a single cell oil rich in docosahexaenoic acid for the production of specialty lipids - Kanno Mathias, Daniela (Array, 2021)
Research background. New sources of docosahexaenoic acid have recently been investigated aiming at infant formula fortification and dietary supplementation, among which the single cell oil with 40–50 % of this acid. Experimental approach. For this purpose, such an oil was blended with caprylic acid in amount substance ratio ranging from 1:1 to 5:1 and the blends were interesterified using either Novozym 435 or Lipozyme TL IM as the catalyst. The influence of the amount of excess free caprylic acid in the substrate, as well as the type of enzyme on the triacylglycerol rearrangement resulting from the synthesis of the structured lipids were evaluated. Results and conclusions. The regiospecific lipase Lipozyme TL IM seemed to induce transesterification among single cell oil triacylglycerols preferably by acidolysis with caprylic acid, which was directly proportional to the ratio of this acid in the substrate. In reactions catalyzed by the non-regiospecific lipase Novozym 435, a higher incorporation of caprylic acid into single cell oil triacylglycerols was observed than when using Lipozyme TL IM, independently of the oil/caprylic acid molar ratio. Novelty and scientific contribution. These results revealed the importance of combining the choice of the type of lipase, either regiospecific or not, with the amount ratios of free fatty acids and the substrate in acidolysis when aiming to produce structured lipids as a source of docosahexaenoic acid.